Estimating global prevalence, incidence, and outcomes of non-alcoholic fatty liver disease from 2000 to 2021: systematic review and meta-analysis. Issue 14 (20th July 2022) - Liu, Jiaye; Tian, Ye; Fu, Xia; Mu, Chunyang; Yao, Menglin; Ni, Yinyun; Liu, Yong; Li, Zhihui
Abstract: Background: The increasing burden of non-alcoholic fatty liver disease (NAFLD) worldwide imposes an emerging public health issue. We perform the current study to estimate the global prevalence, incidence, disease progression, and clinical outcomes of NAFLD. Methods: A systematic search was conducted in Medline, Embase, Web of Science, Google Scholar, and Cochrane CENTRAL that screened articles in English language published from January 2000 to December 2021. NAFLD prevalence, incidence, rate of disease progression, and outcomes were calculated with the DerSimonian-Laird random effects model with arcsine transformation. Results: Our search identified 59, 156 records, of which 578 studies fulfilled our inclusion criteria. The overall prevalence of NAFLD was 29.38% (95% confidence interval [CI] 28.09–30.69) regardless of the diagnostic techniques. Looking at the group in which the diagnosis was made by ultrasound exclusively, the pooled prevalence was 30.49% (95% CI 29.55–31.43). NAFLD has become more prevalent during the year 2011–2021 (31.63%, 95% CI 30.23–33.04) compared with year 2000–2010 (27.94%, 95% CI 26.23–29.69). The pooled estimation of non-alcoholic steatohepatitis prevalence was 8.26% (95% CI 1.13–21.01), 46.49% (95% CI 35.93–57.20), and 46.72% (95% CI 37.57–55.98) in general population, NAFLD patients, and severe/morbidly obese patients, respectively. Based on a total of 110, 142 newly developed NAFLD patients, the pooled incident rate was estimated as 46.24 cases per 1000 person-years (95% CI 43.21–49.30). In patients with NAFLD, the incident rate of hepatocellular carcinoma was 1.46 (95% CI 0.90–2.03) cases per 1000 person-years. The overall pooled estimate of NAFLD related mortality was 23.91 (95% CI 13.55–37.18) death per 1000 person-years. Conclusions: The prevalence of NAFLD is increasing globally. It is contributing to poor clinical outcomes including hepatocellular carcinoma and death. Rising awareness and urgent actions are warranted to control the NAFLD pandemic across the globe. Registration: PROSPERO, No. CRD42020171104.